2015
DOI: 10.1007/s00101-015-0100-0
|View full text |Cite
|
Sign up to set email alerts
|

Intubationslarynxtubus Suction Disposable

Abstract: This first clinical study demonstrated that in patients with apparently normal airways and in the hands of users without previous experience, the iLTS-D allowed sufficient ventilation in all patients and had a high success rate for subsequent endotracheal intubation. The results are, however, preliminary until confirmed by further studies, particularly in patients with difficult airways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
0
4
0
4
Order By: Relevance
“…[678] The recent addition of AAG and i-LTS-D broaden the armamentarium of airway equipment for difficult airway. [12349]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[678] The recent addition of AAG and i-LTS-D broaden the armamentarium of airway equipment for difficult airway. [12349]…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the ILTS-D was found to have a high success rate in a clinical setting for both blind endotracheal intubation and fiber-optically guided intubation. [4] Both SGAs have an integrated gastric access channel. Although the manufacturers for both devices recommend the use of a flexible bronchoscope for intubation, there is not a specific recommendation made regarding the use of these SGAs as a conduit for blind endotracheal intubation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that an oval airway cross section of the tube as seen in the LMA Supreme improved stability of the airway, in comparison to PLMA which had a circular cross section. 30 – 32…”
Section: Specific Eadsmentioning
confidence: 99%
“…Использование ИЛМ (или ларингеальной трубки) для выполнения ИТ или комбинации ИЛМ (или НВУ других модификаций -ларингеальные трубки, ЛМ с возможностью интубации через них) с интубационным ФБС или гибким интубационным видео эндоскопом [64,[95][96][97].…”
Section: комментарии эта методика улучшает визуализацию гортани повunclassified